Determination of the strength of a multilayer BCC lattice structure with face sheets. (March 2019) - Liu, Yabo; Dong, Zhichao; Liang, Jun; Ge, Jingran
Highlights: A 'large unit cell' approach for multilayer BCC lattice structure is proposed. Collapse stress and corresponding strain are analyzed for multilayer structures. Array configuration has a great influence on multilayer structures. Abstract: The body-centered cubic (BCC) lattice, as a type of cellular lattice structure, has been widely researched with the representative volume element (RVE) homogenization method. This ideal theoretical approach requires infinite unit cells in a structure, which is unrealistic and unfeasible with the current manufacturing technology. In this paper, a new theoretical approach considering the effect of array configuration is developed to predict the strength of a multilayer BCC lattice structure. First, the compression behavior of the multilayer BCC lattice structure is analyzed by finite element method (FEM) simulation. Then, an analytical model inspired by the combination of the derived stress-strain curve and the specific contour is built. Predictions of the compression strength are compared with the FEM results for multilayer structures with various spatial array configurations to validate the applicability of the proposed model. And, they are in very good agreement within acceptable errors. Graphical abstract: Image, graphical abstract